2017
DOI: 10.1371/journal.pone.0170208
|View full text |Cite|
|
Sign up to set email alerts
|

The Gut-Brain Axis in Healthy Females: Lack of Significant Association between Microbial Composition and Diversity with Psychiatric Measures

Abstract: ObjectiveThis study examined associations between the composition and diversity of the intestinal microbiota and measures of depression, anxiety, eating disorder psychopathology, stress, and personality in a group of healthy adult females.MethodsFemale participants (n = 91) ages 19–50 years with BMI 18.5–25 kg/m2 were recruited from central North Carolina between July 2014 and March 2015. Participants provided a single fecal sample and completed an online psychiatric questionnaire that included five measures: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 47 publications
(32 citation statements)
references
References 68 publications
1
29
1
1
Order By: Relevance
“…Classification of 16S rRNA forward sequence reads was performed in duplicate with two pipelines: QIIME version 1.5.0, using previously described quality filtering, OTU clustering, and taxonomy assignment methods (Caporaso et al, 2010;Kleiman et al, 2017); and version 2.10.1 of the RDP classifier with a threshold of a 50% RDP score (Wang, Garrity, Tiedje, & Cole, 2007). Both pipelines yielded similar results, with strong separation between patients' samples.…”
Section: Discussionmentioning
confidence: 99%
“…Classification of 16S rRNA forward sequence reads was performed in duplicate with two pipelines: QIIME version 1.5.0, using previously described quality filtering, OTU clustering, and taxonomy assignment methods (Caporaso et al, 2010;Kleiman et al, 2017); and version 2.10.1 of the RDP classifier with a threshold of a 50% RDP score (Wang, Garrity, Tiedje, & Cole, 2007). Both pipelines yielded similar results, with strong separation between patients' samples.…”
Section: Discussionmentioning
confidence: 99%
“…In this sample, we also observed a significant correlation between mood and microbial diversity such that lower diversity was associated with higher self‐report depression scores . Of note, this was not observed in an independent sample of healthy controls who had a much more restricted range of responses on the mood measures . Together, these observations raised the question of whether this aspect of the microbe–gut–brain axis is only detectable at more extreme levels of psychopathology.…”
Section: Formative Workmentioning
confidence: 93%
“…98 Of note, this was not observed in an independent sample of healthy controls who had a much more restricted range of responses on the mood measures. 99 Together, these observations raised the question of whether this aspect of the microbe-gut-brain axis is only detectable at more extreme levels of psychopathology. A recent large population investigation provided intriguing and replicated evidence for an association between the gut microbiome and quality of life and depression.…”
Section: Clinical Neurosciencesmentioning
confidence: 99%
“…A small investigation suggested evidence of dysbiosis in anxiety and depression patients and paired with increased gut permeability (Stevens et al, ). While another study failed to find an association between anxiety and depressive symptoms and microbial diversity in healthy females (Kleiman et al, ). A recent study in generalized anxiety disorder revealed reduced microbial richness and diversity in drug‐naïve ( n = 12) and medicated patients ( n = 28) compared to controls ( n = 36; H. Y. Jiang et al, ).…”
Section: The Microbiome In Clinical Populationsmentioning
confidence: 99%